Effects of chromophore interaction in photophysics and photochemistry of cyanine dyes - A. S. Tatikolov; Zh. A. Krasnaya; L. A. Shvedova; V. A. Kuzmin (International Journal of Photoenergy)
Spectral and fluorescent properties of ketocyanine dyes (polyenic bis-ω,ω′-aminoketones) and cation-anionic polymethine dyes of various structures were studied. The symmetric ketocyanines were shown to have a long-wavelength absorption band bathochromically shifted in comparison with that of the asymmetric ketocyanines with the same total length of the polyenic chain. The nonlinear ketocyanines exhibit the additional short-wavelength band in their absorption spectra, which can be more intense than the longwavelength band. The absorption spectra of ion pairs of cation-anionic dyes with overlapping cation and anion bands contain a new intense short-wavelength band inactive in fluorescence excitation. These spectral peculiarities are explained on the basis of chromophore interaction model. It has also been shown that the T1 levels of ketocyanine chromophores do not essentially interact with each other in a ketocyanine molecule in nonpolar solvents; in polar solvents this interaction becomes appreciable due to lowering the potential barrier for conjugation.